RANBP2 mutation causing autosomal dominant acute necrotizing encephalopathy attenuates its interaction with COX11. (15th October 2021) - Shibata, Akiko; Kasai, Mariko; Hoshino, Ai; Tanaka, Teruyuki; Mizuguchi, Masashi
Highlights: A nuclear pore protein, Ran-binding protein2 (RANBP2), regulates mitochondrial function. RANBP2 binds to COX11 and promotes glucose metabolism. RANBP2 mutations cause autosomal dominant acute necrotizing encephalopathy (ADANE). This study showed an attenuated interaction of mutated RANBP2 with COX11. Whether energy metabolism is altered in neural cells remains to be demonstrated. Abstract: Purpose: Autosomal dominant acute necrotizing encephalopathy (ADANE) is caused by missense mutations in the gene encoding Ran-binding protein 2 (RANBP2), a nuclear pore protein regulating mitochondrial localization and function. Previous studies have found that RANBP2 binds to COX11 and suppresses its inhibitory activity over hexokinase1. To further elucidate mitochondrial dysfunction in ADANE, we analyzed the interaction between mutated RANBP2 and COX11. Methods: We extracted cDNA from a patient and constructed pGEX wild-type or mutant-type vectors including RANBP2 c.1754C>T, the commonest variant in ADANE. We transformed E. coli competent cells with the vectors and had them express GST-RANBP2 recombinant protein, and conducted a pull-down assay of RANBP2 and COX11. Results: The amount of COX11 bound to mutated RANBP2 was significantly smaller than that bound to the wild-type RANBP2. Conclusion: Mutated RANBP2 had an attenuated binding ability to COX11. Whether this change indeed decreases ATP production remains to be further explored.